Developing a Model for Enhancing Responsibility Values of Prathomsuksa 5 Students - ศิริโสภณภิวัฒน์, ศุภมิต; ปิยะกุล, อารยา (Ratchaphruek Journal, 2017)
ABSTRACT This research aimed 1) to study the components and behavioral indicators of responsibility value of students, 2) to develop the model for enhancing the responsibility value of students and 3) to stud the results of the model for enhancing the responsibility value of Prathomsuksa 5 students. A sample of 20 cases was drawn from Prathomsuksa 5 students using Multi-stage sampling technique. Instruments of this study were the model for enhancing the responsibility values of students and responsibility value assessment form. Data were analyzed using mean, standard deviation, and One Way Repeated Measure ANOVA. The findings are as follows: 1. Components of responsibility valu consisted of 3 components, which were 1) knowledge and understanding of responsibility value, 2) beliefs in being responsible, and 3) expression of responsibility. There were 4 behavioral indicators which were consisted of knowing duty, compliance with regulations, effort to achieve task, and acceptance the effects of actions on themselves and others. 2. Model for enhancing the responsibility value of students consisted of 4 components which were 1) concepts and basic theories, 2) objectives of the model and 3) the steps o enhancing the responsibility value 4) measurement and evaluation. The suitability of the model assessed by experts was at the highest level. 3. Results of implementing the model for enhancing the responsibility value of students showed that; students have higher responsibility values which the mean of scores after the end of activities and follow-up period were higher than mean scores before doing activities period at the statistical significant level of .05.